Assessment of oral health and prevalence of oral conditions in human immunodeficiency virus-infected subjects visiting antiretroviral therapy centers - Wagisha Barbi; Kumari Shalini; Anjali Kumari; Vaibhava Raaj; Hitesh Gupta; Preeti Gauniyal; Priyadarshini Rangari (Wolters Kluwer Medknow Publications, 2021)
Background: Weakened immune system from acquired immunodeficiency syndrome (AIDS) makes the individual prone to various opportunistic infections which are life-threatening including various carcinomas and disorders affecting the neurological system. Aims: The present trial was done to assess the prevalence of oral presentations and treatment needs in AIDS/human immunodeficiency virus (HIV)-infected subjects visiting antiretroviral therapy centers. Materials and Methods: The study included 126 subjects. Oral cavity was assessed and dentition, periodontal condition, and lesions and conditions affecting the oral mucosa were identified along with their treatment needs. The collected data were subjected to statistical evaluation and the results were formulated. Results: Candidiasis was seen in 25.39% (n = 32) of total subjects. Concerning the periodontal status of HIV-infected study population, it was seen that maximum attachment loss both in males and females was within the range of 0-3 mm. Regarding decayed, missing, and filled teeth scores, these were statistically significantly higher in males (P = 0.001). Conclusion: The present study concluded that the majority of subjects infected with HIV present one or more oral presentation and lesion, with candidiasis being the most common condition.